2014
DOI: 10.1080/14786419.2014.952232
|View full text |Cite
|
Sign up to set email alerts
|

In vitroantimicrobial activity ofPistacia lentiscusL. edible oil and phenolic extract

Abstract: Pistacia lentiscus L. is known in some Tunisian forest area by its fixed oil used in traditional medicine as an antiseptic product. This investigation is the first to study the antimicrobial activity of P.lentiscus edible oil and its phenolic extract. Oil was extracted from fruits harvested from six provenances located in Tunisia. The antimicrobial activity was tested using disc diffusion assay and the broth dilution method. Kbouch and Sidi Zid oils were most efficient (p < 0.003) against, respectively, Staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 10 publications
1
23
1
Order By: Relevance
“…The plant’s location, climatic conditions and soil composition could explain the fact that the Sardinian LBO activity against S. aureus described in our study was not found in previous studies performed using Tunisian LBO ( Mezni et al, 2014a , 2016 ).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The plant’s location, climatic conditions and soil composition could explain the fact that the Sardinian LBO activity against S. aureus described in our study was not found in previous studies performed using Tunisian LBO ( Mezni et al, 2014a , 2016 ).…”
Section: Discussioncontrasting
confidence: 54%
“…Each part shows different proprieties: mastic gum (produced on the island of Chios) is active against Helicobacter pylori infection, while the leaf-essential oil affects different bacterial species including some oral pathogens such as: Porphyromonas gingivalis, Streptococcus mutans, Streptococcus gordonii, Fusobacterium nucleatum, Prevotella intermedia ( Pham-Huy et al, 1999 ; Koutsoudaki et al, 2005 ; Aksoy et al, 2006 ). The oil produced by pressing the berries represents the liquid fraction at room temperature and the antimicrobial activity of lentisk oil obtained from the berries (LBO) on Staphylococcus aureus and Aspergillus niger it has recently been reported ( Mezni et al, 2014a , 2016 ). At present, few studies exist on the interactions of LBO with microorganisms and on its antimicrobial mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in agreement with previous studies. P. lentiscus is considered to be an antimicrobial plant [53,54], and ethanolic extracts of its fruits and leaves are used as ingredients in pork sausage to reduce microbial spoilage [55]. Some studies found that organic extracts of C. colocynthis are more active in comparison to aqueous extracts [47] and that hydromethanolic extracts are less toxic against F. oxysporum and its enzymes (CMCase, pectinase, and protease) [56] and exhibit a moderate antifungal activity against A. fumigatus DSM790 and A. niger DSM1988 [57].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alphitolic acid a triterpenoid identified from leaves is a significant antibiofilm against S. mutans, a causative agent of human dental caries (Damiano et al, 2017). In the literature, several studies have proved the inhibitory effect of phenolic compounds and flavonoids on microbial strains; it has been reported that Gram-positive bacteria are hypersensitive to herb essences than Gram-negative due to hydrophobic lipopolysaccharide in the outer membrane that protects various factors (Mezni et al, 2015;Ferreira et al, 2012). Staphylococcus aureus ATCC 25923 6,5 ± 0,17 6,5 ± 0,2 8 ± 0,8 6,5 ±0,6 9 ±1,0 7 ±0,33 9 ±2,5 22…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%